Rapid prototyping using robot welding: slicing system developmens - Ribeiro, A. Fernando (1996)
With direct deposition of metal a new Rapid Prototyping process had been developed at Cranfield University in the last couple of years. The process entails the use of a Gas Metal Arc fusion welding robot which deposits successive layers of metal in such way that it forms a 3D solid component. First, a solid model is drawn using a CAD system, then data indicating the kind of layers and dimension is incorporated and the solid is automatically sliced. This slicing routine also generates reports on the welding time and conditions for the production of the component and automatically generates the robot program. The slicing routines used in traditional rapid prototyping processes did not cope with this welding deposition technique and therefore a new slicing process was developed specificaly for this process. A few attempts had been made before getting to the final solution. All these attempts are described in this paper as well as the final solution.